Self-correction, control and accountability in the ancient Melaka Kingdom (1401–1511 AD) - Mustafa, Hasri; Ibrahim, Mohd Ikhwan (Emerald, 2023)
Purpose – The purpose of this paper is to study the governance structure in the ancient Melaka Kingdom (1401–1511 AD) using historical Hukum Kanun Melaka (the Land Law) and Undang-Undang Laut Melaka (the Maritime Law). The focus is on self-correction, control and accountability that were used to preserve the peace and well-being of society and the overall harmony of the community during the period. Design/methodology/approach – The study employs close readings to discover and identify implicit formal and thematic elements of the texts into a meaningful enactment. The study is based on historical archival research at the National Archives of Malaysia and at the National Library of Malaysia. Findings – Though classical, the underlying accounting practices were shown to consummate in an articulated model of measurement activities based on specific proportion of gold in tahil measurement, used for slaves, free men and stolen animal and property value. Controls were established through punishment and penalty. Accountability functioned in different levels and degrees hierarchically and horizontally. Research limitations/implications – The study excludes the improved sections of the laws that are based on the Islamic perspective. The discussion is limited to the indigenous adat sections of laws only although the sections may inseparable with the Hindu/Buddhist tradition. Originality/value – A study of these classical laws would be a reference for accounting publication in the Malay world which has been stationed in the gallery for many years, awaiting discovery.